Making sense of the entrepreneurial university - A social constructionist view - Paasio Kaisu (University of Turku, 2022)
For quite some time, the entrepreneurial university has been a significant subject of scholarly, policy and practical interests. While universities are increasingly urged to become entrepreneurial, previous research has focused on portraying what entrepreneurial universities are and what they do, or should do, in contrast to other universities. In addition, a number of entrepreneurial university models propose different paths and activities for the entrepreneurial transformation. Admittedly, research has provided plenty of knowledge about the phenomenon, yet the viewpoint tends to be rather structural and functional, which calls for new approaches and perspectives in researching entrepreneurial universities.
In this study, I take a critical stance towards the mainstream research of the entrepreneurial university and add to our understanding from a fresh perspective by zooming in to the university to focus on the lived experience of university personnel and setting individuals as units of analysis. This study builds on social constructionism, applying narrative methodology and a sensemaking lens to investigate how an entrepreneurial university is constructed from within the university. Voice is given to personnel in a university that has a strategic commitment to becoming entrepreneurial, and their stories are told through my interpretation.
The research material consists of group discussions in which the study participants discuss entrepreneurship in the university context broadly. An unstructured interview method was employed with an eye to giving plenty of room for the participants’ spontaneous narration and storytelling. In the analysis, attention was given to the intertwinement of storytelling and sensemaking. I focused on how the university personnel talked about entrepreneurship in the university and what kinds of meanings they gave to entrepreneurship, university and the entrepreneurial university.
As an outcome of this study, I present six stories of sensemaking and four local entrepreneurial university metanarratives that derived from these stories and the sensemaking processes. The six stories provide different perspectives on the entrepreneurial university, in which the sensemaking process variously covers participants’ interpretations of entrepreneurship, negotiation about a university, reflection on the everyday work at the university and a critical consideration of the strategic vision of the university. The entrepreneurial university metanarratives – here named ‘much ado about nothing’, ‘members’ club’, ‘progress’ and ‘illusion’ – further address the plurivocality of the phenomenon, that instead of one, there are many understandings of the entrepreneurial university that coexist concurrently within the university.
The results of this study indicate that the entrepreneurial transformation not only concerns the structures and functions of a university, but also is a matter of the university personnel’s collective sensemaking. This study thus makes a theoretical contribution by providing a new, alternative perspective to the entrepreneurial university conceptualization. It is more nuanced and aligned with the internal and contextual aspects of the phenomenon and critical in the sense that it is attentive to the prevailing interpretations of an entrepreneurial university that tend to be rather stagnant and dualistic. The methodological contribution of this study comes from the use of the sensemaking lens in exploring the lived experience of university personnel as they negotiate the entrepreneurial transformation and construct their understanding about the entrepreneurial university, which allows for a deeper interpretative understanding of the phenomenon. The discussion of the results also advances our understanding concerning the practical implementation of transformation efforts, highlighting the need to understand and make sense of a new strategy as critical elements of engagement.
Overall, the thesis contributes to entrepreneurial university research and discussion with novel theoretical, methodological and empirical results and adds to the existing knowledge of the interpretive literature on the entrepreneurial university.